Environment-friendly low-smoke halogen-free fireproof power flexible cable

By using an outer sheath layer made of environmentally friendly materials such as halogen-free polyolefins in the cable, the problem of smoke and toxic gas emissions during combustion of traditional cables is solved, and efficient flame retardant and insulation performance is achieved, ensuring environmental protection and human health .

CN119463348APending Publication Date: 2025-02-18KUNMING MINGCHAO ELECTRIC CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656056.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional wires and cables will produce a large amount of smoke and toxic gases when burned, causing serious impacts on the environment and human health.

Method used

An environmentally friendly low-smoke, halogen-free fire-resistant powered soft cable is adopted, which includes a cable core, an insulating layer and an outer sheath layer. The outer sheath layer is made of halogen-free polyolefin, polyvinyl chloride, talc, calcium carbonate, flame retardant , antioxidants and polybenzimidazole are made of raw materials, and are formed by high shear mixing and twin screw extruder.

Benefits of technology

While meeting the insulation performance, the cable improves flexibility and tensile resistance, and has excellent flame retardant and insulation properties, which can effectively reduce smoke and toxic gas emissions during fire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an environment-friendly low-smoke halogen-free fireproof power flexible cable which comprises a cable core, an insulating layer and an outer sheath layer, the insulating layer wraps the outer surface of the cable core, the outer sheath layer wraps the outer surface of the insulating layer, and the outer sheath layer wraps the outer surface of the outer sheath layer. An ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talcum powder, calcium carbonate, aluminum hydroxide, magnesium hydroxide, spiro aryl phosphate, trioctyl trimellitate, an antioxidant 1010, tris [2, 4-di-tert-butylphenyl] phosphite, a calcium-zinc stabilizer, polybenzimidazole and a coloring agent are mixed and subjected to extrusion molding, and the outer protective sleeve is prepared; the outer surface of the cable core is coated with the insulating layer, and then the outer surface of the insulating layer is coated with the outer protective sleeve, so that the environment-friendly low-smoke halogen-free fireproof power flexible cable is prepared. During combustion, no halogen acid gas is released, the smoke amount is low, and smoke and toxic gas cannot be generated after fire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable manufacturing, in particular to an environmentally friendly low-smoke, halogen-free and fire-resistant power flexible cable. Background Art

[0002] With increasing environmental awareness, higher requirements are being placed on the safety and environmental performance of wires and cables. Conventional wires and cables produce large amounts of smoke and toxic gases when burned, severely impacting the environment and human health. Therefore, developing a new, environmentally friendly, low-smoke, halogen-free, fire-resistant flexible power cable formula to reduce smoke and toxic gas emissions during fires is of great practical significance. Summary of the Invention

[0003] The object of the present invention is to provide an environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable, comprising a cable core, an insulation layer, and an outer sheath layer, wherein the insulation layer is coated on the outer surface of the cable core, and the outer protective sheath is coated on the outer surface of the insulation layer. The outer protective sheath is made of the following raw materials in parts by weight, including: Halogen-free polyolefin: 60 to 70 parts Polyvinyl chloride: 10 to 20 parts Talc: 5 to 15 parts Calcium carbonate: 5 to 10 parts flame retardants Trioctyl trimellitate: 10 to 15 parts Antioxidant 1010: 0.5 to 2.8 parts Antioxidant: 0.1 to 1 part Calcium zinc stabilizer: 1.5 to 3 parts Polybenzimidazole: 6 to 8 parts Colorant: 0.1 to 0.5 parts; The halogen-free polyolefin is a mixture of ethylene-vinyl acetate copolymer (EVA) and high-density polyethylene (HDPE); The flame retardant is a mixture of aluminum hydroxide, magnesium hydroxide and spirocyclic aryl phosphate flame retardant, wherein the ratio of aluminum hydroxide to magnesium hydroxide is 1:1; the flame retardant is 30 to 40 parts of aluminum hydroxide and magnesium hydroxide in total, and 0.5 to 2 parts of the spirocyclic aryl phosphate flame retardant; The polybenzimidazole is an anti-ultraviolet agent. Polybenzimidazole has full-color ultraviolet absorption and can be used as a light stabilizer to improve the anti-ultraviolet performance of the outer protective sheath. The antioxidant 1010 is a phenolic antioxidant, and the auxiliary antioxidant is tris[2,4-di-tert-butylphenyl]phosphite; The colorant is an inorganic pigment.

[0004] Furthermore, the ratio of the ethylene-vinyl acetate copolymer and high-density polyethylene mixture is 3:1.

[0005] Furthermore, the talc powder is ultrafine talc powder with a mesh size of 1250 meshes.

[0006] Furthermore, the cable core is made of high-purity oxygen-free copper, and the cable core is a plurality of round copper soft single wires twisted together.

[0007] Furthermore, the insulating layer is made of low-temperature wear-resistant modified silicone rubber material.

[0008] Furthermore, the steps of preparing the outer protective cover include the following: Step 1: Prepare the ingredients Weigh all raw materials according to the recipe to ensure accuracy; Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talc, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite, then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 60-80°C, start the high shear mixer for preliminary mixing, mix for 20-30 minutes, until the mixture is uniform, then discharge; Step 4: Extrusion The evenly mixed material is fed into a twin-screw extruder. The screw speed of the twin-screw extruder is set to 60-100 rpm, the temperature of the feed section is set to 150-160°C, the compression section is set to 160-170°C, the metering section is set to 170-180°C, and the die head is set to 180-190°C. After extrusion, the material is cooled through a cooling water tank. The cooling water temperature is about 20-30°C.

[0009] The beneficial effects of the present invention are embodied in: The cable prepared by the present invention enhances the flexibility and tensile strength of the cable itself while meeting the insulation performance of the cable, and at the same time has excellent flame retardant and insulating properties, and can effectively reduce smoke and toxic gas emissions in the event of a fire. DETAILED DESCRIPTION

[0010] The present invention is further described below with reference to the following examples. The examples are not intended to limit the scope of the present invention. Modifications or substitutions made to the methods, steps, or conditions of the present invention without departing from the essence of the technical solution of the present invention are within the scope of the present invention.

[0011] Unless otherwise specified, the equipment, devices and process methods used in the examples are conventional equipment, devices and process methods well known to those skilled in the art.

[0012] An environmentally friendly low-smoke halogen-free fireproof power flexible cable, comprising a cable core, an insulation layer and an outer sheath layer, wherein the insulation layer is coated on the outer surface of the cable core, and the outer protective sheath is coated on the outer surface of the insulation layer. The outer protective sheath is made of the following raw materials in parts by weight: 60 to 70 parts of halogen-free polyolefin, 10 to 20 parts of polyvinyl chloride, 5 to 15 parts of talc, 5 to 10 parts of calcium carbonate, flame retardant, 10 to 15 parts of trioctyl trimellitate, 0.5 to 2.8 parts of antioxidant 1010, 0.1 to 1 part of auxiliary antioxidant, 1.5 to 3 parts of calcium zinc stabilizer, 6 to 8 parts of polybenzimidazole, and 0.1 to 1 part of colorant. 0.5 parts, the halogen-free polyolefin is a mixture of ethylene-vinyl acetate copolymer (EVA) and high-density polyethylene (HDPE); the flame retardant is a mixture of aluminum hydroxide, magnesium hydroxide and spirocyclic aromatic phosphate flame retardant, and the ratio of aluminum hydroxide to magnesium hydroxide is 1:1; the flame retardant is 30 to 40 parts of aluminum hydroxide and magnesium hydroxide in total, and the spirocyclic aromatic phosphate flame retardant is 0.5 to 2 parts; polybenzimidazole is an anti-ultraviolet agent, polybenzimidazole has full-color ultraviolet absorption, and can be used as a light stabilizer to improve the anti-ultraviolet performance of the outer protective cover; the antioxidant 1010 is a phenolic antioxidant, and the auxiliary antioxidant is tris [2,4-di-tert-butylphenyl] phosphite; the colorant is an inorganic pigment.

[0013] Among them, the ratio of ethylene-vinyl acetate copolymer and high-density polyethylene mixture is 3:1; the talcum powder is ultrafine talcum powder with a mesh size of 1250; the cable core material is high-purity oxygen-free copper, and the cable core is a plurality of round copper soft single wires twisted together; the insulation layer is a low-temperature wear-resistant modified silicone rubber material.

[0014] Example 1

[0015] The steps for preparing the outer protective cover include the following: Step 1: Prepare the ingredients Weigh all the raw materials according to the formula to ensure accuracy, and weigh 45 kg of ethylene-vinyl acetate copolymer, 15 kg of high-density polyethylene, 10 kg of polyvinyl chloride, 12 kg of talc, 5 kg of calcium carbonate, 15 kg of aluminum hydroxide, 15 kg of magnesium hydroxide, 0.5 kg of spirocyclic aryl phosphate, 10 kg of trioctyl trimellitate, 0.5 kg of antioxidant 1010, 0.1 kg of tris[2,4-di-tert-butylphenyl]phosphite, 1.5 kg of calcium zinc stabilizer, 6 kg of polybenzimidazole, and 0.1 kg of colorant; Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talc, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite, then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 60°C, start the high shear mixer for preliminary mixing, mix for 20 minutes, and then discharge until the mixture is evenly mixed; Step 4: Extrusion The evenly mixed material is fed into a twin-screw extruder, the screw speed of the twin-screw extruder is set to 60 rpm, the feed section temperature is set to 150°C, the compression section is set to 160°C, the metering section is set to 170°C, the die head is set to 180°C, and after extrusion, it is cooled through a cooling water tank with a cooling water temperature of about 20°C to prepare an outer sheath layer.

[0016] Example 2

[0017] The steps for preparing the outer protective cover include the following: Step 1: Prepare the ingredients Weigh all the raw materials according to the formula to ensure accuracy, and weigh 47 kg of ethylene-vinyl acetate copolymer, 16 kg of high-density polyethylene, 13 kg of polyvinyl chloride, 15 kg of talc, 7 kg of calcium carbonate, 16.5 kg of aluminum hydroxide, and 16.5 kg of magnesium hydroxide. Then weigh 1 kg of spirocyclic aromatic phosphate, 12 kg of trioctyl trimellitate, 1.3 kg of antioxidant 1010, 0.4 kg of tris[2,4-di-tert-butylphenyl]phosphite, 2 kg of calcium zinc stabilizer, 6.5 kg of polybenzimidazole, and 0.3 kg of colorant. Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talc, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite, then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 70°C, start the high shear mixer for preliminary mixing, mix for 23 minutes, and then discharge until the mixture is evenly mixed; Step 4: Extrusion The evenly mixed material was fed into a twin-screw extruder, the screw speed of the twin-screw extruder was set to 75 rpm, the temperature of the feed section was set to 155°C, the compression section was set to 165°C, the metering section was set to 175°C, and the die head was set to 185°C. After extrusion, the material was cooled in a cooling water tank, and the cooling water temperature was about 25°C to prepare an outer sheath layer.

[0018] Example 3

[0019] The steps for preparing the outer protective cover include the following: Step 1: Prepare the ingredients Weigh all the raw materials according to the formula to ensure accuracy, and weigh 50 kg of ethylene-vinyl acetate copolymer, 17 kg of high-density polyethylene, 16 kg of polyvinyl chloride, 8 kg of talc, 9 kg of calcium carbonate, 18 kg of aluminum hydroxide, and 18 kg of magnesium hydroxide. Then weigh 1.5 kg of spirocyclic aromatic phosphate, 14 kg of trioctyl trimellitate, 2.1 kg of antioxidant 1010, 0.9 kg of tris[2,4-di-tert-butylphenyl]phosphite, 2.5 kg of calcium zinc stabilizer, 7.5 kg of polybenzimidazole, and 0.4 kg of colorant. Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talc, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite, then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 70°C, start the high shear mixer for preliminary mixing, mix for 23 minutes, and then discharge until the mixture is evenly mixed; Step 4: Extrusion The evenly mixed material was fed into a twin-screw extruder, the screw speed of the twin-screw extruder was set to 85 rpm, the feed section temperature was set to 155°C, the compression section temperature was set to 165°C, the metering section temperature was set to 175°C, and the die head temperature was set to 185°C. After extrusion, the material was cooled in a cooling water tank, and the cooling water temperature was about 25°C to prepare an outer sheath layer.

[0020] Example 4

[0021] The steps for preparing the outer protective cover include the following: Step 1: Prepare the ingredients Weigh all the raw materials according to the formula to ensure accuracy, and weigh 53 kg of ethylene-vinyl acetate copolymer, 17 kg of high-density polyethylene, 20 kg of polyvinyl chloride, 8 kg of talc, 10 kg of calcium carbonate, 20 kg of aluminum hydroxide, 20 kg of magnesium hydroxide, and then weigh 2 kg of spirocyclic aromatic phosphate, 15 kg of trioctyl trimellitate, 2.8 kg of antioxidant 1010, 1 kg of tris[2,4-di-tert-butylphenyl]phosphite, 3 kg of calcium zinc stabilizer, 8 kg of polybenzimidazole, and 0.5 kg of colorant; Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talc, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite, then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 80°C, start the high shear mixer for preliminary mixing, mix for 23 minutes, and then discharge until the mixture is uniform; Step 4: Extrusion The evenly mixed material was fed into a twin-screw extruder, the screw speed of the twin-screw extruder was set to 100 rpm, the temperature of the feed section was set to 160°C, the compression section was set to 1705°C, the metering section was set to 180°C, and the die head was set to 190°C. After extrusion, the material was cooled in a cooling water tank, and the cooling water temperature was about 30°C to prepare an outer sheath layer.

[0022] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

Claims

1. An environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable, comprising a cable core, an insulating layer and an outer sheath layer, wherein the insulating layer is coated on the outer surface of the cable core, and the outer protective sheath is coated on the outer surface of the insulating layer, characterized in that The outer protective cover is made of the following raw materials in parts by weight: Halogen-free polyolefin: 60 to 70 parts Polyvinyl chloride: 10 to 20 parts Talc: 5 to 15 parts Calcium carbonate: 5 to 10 parts Flame retardants Trioctyl trimellitate: 10 to 15 parts Antioxidant 1010: 0.5 to 2.8 parts Antioxidant: 0.1 to 1 part Calcium zinc stabilizer: 1.5 to 3 parts Polybenzimidazole: 6 to 8 parts Colorant: 0.1 to 0.5 parts; The halogen-free polyolefin is a mixture of ethylene-vinyl acetate copolymer (EVA) and high-density polyethylene (HDPE); The flame retardant is a mixture of aluminum hydroxide, magnesium hydroxide and spirocyclic aryl phosphate flame retardant, wherein the ratio of aluminum hydroxide to magnesium hydroxide is 1:1; the flame retardant is 30 to 40 parts of aluminum hydroxide and magnesium hydroxide in total, and 0.5 to 2 parts of the spirocyclic aryl phosphate flame retardant; The polybenzimidazole is an anti-ultraviolet agent. Polybenzimidazole has full-color ultraviolet absorption and can be used as a light stabilizer to improve the anti-ultraviolet performance of the outer protective cover. The antioxidant 1010 is a phenolic antioxidant, and the auxiliary antioxidant is tris[2,4-di-tert-butylphenyl]phosphite; The colorant is an inorganic pigment.

2. The environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable according to claim 1, characterized in that: The ratio of the ethylene-vinyl acetate copolymer to the high-density polyethylene mixture is 3:

1.

3. The environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable according to claim 1, characterized in that: The talcum powder is ultrafine talcum powder with a mesh size of 1250 meshes.

4. The environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable according to claim 1, characterized in that: The cable core is made of high-purity oxygen-free copper, and the cable core is a plurality of round copper soft single wires twisted together.

5. The environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable according to claim 1, characterized in that: The insulating layer is made of low-temperature wear-resistant modified silicone rubber material.

6. The environmentally friendly low-smoke, halogen-free, fire-resistant power flexible cable according to claim 1, characterized in that: The steps of preparing the outer protective cover include the following: Step 1: Raw material preparation Weigh all ingredients according to the recipe to ensure accuracy; Step 2: Preliminary mixing In a mixing barrel, mix ethylene-vinyl acetate copolymer, high-density polyethylene, polyvinyl chloride, talcum powder, calcium carbonate, aluminum hydroxide, and magnesium hydroxide weighed in proportion, and then add spirocyclic aryl phosphate and trioctyl trimellitate in sequence, and then add antioxidant 1010 and tris[2,4-di-tert-butylphenyl]phosphite after mixing, and then add calcium zinc stabilizer and polybenzimidazole, mix well, and finally add colorant; Step 3: Mixing Put all the raw materials after preliminary mixing into a high shear mixer, set the temperature of the high shear mixer to 60-80°C, start the high shear mixer for preliminary mixing, mix for 20-30 minutes, and then discharge until the mixture is evenly mixed; Step 4: Extrusion The evenly mixed material is fed into a twin-screw extruder, the screw speed of the twin-screw extruder is set to 60-100rpm, the feed section temperature is set to 150-160°C, the compression section is set to 160-170°C, the metering section is set to 170-180°C, the die head is set to 180-190°C, and after extrusion, it is cooled through a cooling water tank, and the cooling water temperature is about 20-30°C.